Functionalized Graphenes and Thermoplastic Nanocomposites Based upon Expanded Graphite Oxide - Steurer, Peter; Wissert, Rainer; Thomann, Ralf; Mülhaupt, Rolf (Macromolecular rapid communications., 2009)
Exfoliation of expanded GO represents an attractive route to functionalized graphenes as versatile 2D carbon nanomaterials and components of a wide variety of polymer nanocomposites. Thermally reduced graphite oxides (TrGO) with specific surface areas of 600 to 950 m2 · g−1 were obtained by oxidation of graphite followed by thermal expansion at 600 °C. Thermal post treatment at 700 °C and 1 000 °C increased carbon content (81 to 97 wt.‐%) and lowered resistivity (1 600 to 50 Ω · cm). During melt extrusion with PC, iPP, SAN and PA6, exfoliation afforded uniformly dispersed graphenes with aspect ratio > 200. In comparison to conventional 0D and 1D carbon nanoparticles, TrGO afforded nanocomposites with improved stiffness and lower percolation threshold. Recent progress and new strategies in development of functionalized graphenes and graphene‐based nanocomposites are highlighted.